Analisis Verba Transitif dan Intransitif dalam Cerita Pendek “Al-Athfal Wa Al-Qiro’ah” - Malida, Alya (Research Community for Critical Society and Environment, 2024)
In terms of syntax, verbs can be distributed together with other grammatical units so that a verb distribution is formed that can become the core element of a phrase. There are several subcategories for verbs. Predicate verbs in Indonesian can be divided into two types, namely intransitive verbs and transitive verbs. This study aims to determine whether these verbs are used by the rules of Arabic grammar (syntax). This research method uses a qualitative descriptive analysis method. The data collection technique in this study is by reading and recording. The data source is in the short story